A evolução e os novos instrumentos de financiamento privado do agronegócio brasileiro: um estudo exploratório - Palermo, Daniela Moreira (2006)
During the last two decades, Brazil has been consistently increasing its participation in agribusiness worldwide. Currently, we re the main producer and exporter of lots of agricultural products, reason for why this sector reached prime importance in Brazilian economy. The question that drives this study is the financing need that comes along with this recent agribusiness growth. The objective here is to examine and analyze main agribusiness private financing instruments that are being currently used, with special attention to the new financing instruments regulated by Law 11.076/2004. The study starting point was the creation of Rural Credit National System, in 1965. The evolution analysis of this System during the following four decades was vital to understand agribusiness public financing situation and the arising need of new private sources of fund raising. Agribusiness financing private instruments were object of theoretical and practical analyzes, through applicable legislation and characteristics, over and above the negotiations registered in clearing and custody systems, respectively. The study allowed us to conclude that there is an explicit and unquestioned need of increasing agribusiness financing alternatives, and that new legislation was an important step toward consolidation of a new auto financing system for the participants of agribusiness chain, in order to decrease the dependence of public financing resources